Perlindungan Konsumen Muslim Dalam Labelisasi Halal: Analisis UU Jaminan Produk Halal (JPH) dan Maqashid Syariah - Nafila, Yusratun - (Maliki Interdisciplinary Journal, 2026)
This research report analyzes the dynamics of Muslim consumer protection in Indonesia after the change in the halal certification regime from voluntary to mandatory as stipulated in the JPH Law, the Job Creation Law, and PP 39/2021. Through the approach of Maqashid Shariah, especially the principles of Hifz al-Din, Hifz al-Nafs, Hifz al-Aql, and Hifz al-Mal. This study evaluates the effectiveness of the legal framework in ensuring the certainty and safety of halal products. The analysis highlights the tension between the need for ease of doing business through self-declaration schemes for MSEs and the demand for legal certainty for consumers, with the case of Nabidz's "wine" certification as an important illustration of the regulatory loophole that has the potential to harm people's spiritual rights. This study also assesses the readiness of the national halal ecosystem ahead of the implementation of halal certification obligations for medium-large industries in 2024 and the postponement for MSEs until 2026. The findings show that although the legal structure has been relatively robust, its implementation still leaves uncertainty so that more integrative supervision and effective sanctions enforcement are needed to ensure more comprehensive consumer protection.